An increased expression profile of Th9/IL-9 correlated with Th17/IL-17 in patients with immune thrombocytopenia. (3rd April 2017) - Qiao, Jianlin; Li, Xiaoqian; Wu, Yulu; Wu, Xiaoqing; Zhu, Feng; Liu, Na; Qi, Kunming; Cheng, Hai; Li, Depeng; Sun, Haiying; Zeng, Lingyu; Xu, Kailin
Abstract: Immune thrombocytopenia (ITP) is a heterogeneous autoimmune disease, characterized by dysregulation of cellular immunity. Th9 cells were recently identified as a new subtype of Th cells, characterized by preferential production of IL-9. Given the pleiotropic function of IL-9, Th9 cells are demonstrated to be involved in various autoimmune diseases. However, whether Th9 cells are involved in the pathogenesis of ITP remains unclear. In this study, 49 active ITP patients, 39 ITP with remission and 20 healthy controls were included. Peripheral blood mononuclear cells (PBMCs) were isolated from ITP and controls for measuring Th9 and Th17 cells by flow cytometry. Meanwhile, RNA was isolated from PBMCs for the measurement of the mRNA level of PU.1, IRF4, BATF, and RORγt by quantitative real-time PCR. Plasma levels of IL-9 and IL-17 were detected by ELISA. Our results showed that higher expressions of Th9, IL-9, and associated transcription factors (PU.1, IRF4, and BATF) were found in active ITP patients and restored to the normal level (except IL-9) in patients in remission. Meanwhile, Th9 cells and the IL-9 plasma level were positively correlated with Th17 cells and the IL-17 level in ITP patients, respectively. Moreover, a positive correlation of IRF4 or BATF with RORγt was found. In conclusion, an aberrant expression profile of Th9/IL-9 was associated with pathogenesis of ITP possibly through cooperatively working with Th17/IL-17 and therapeutically targeting Th9/IL-9 might be a novel approach in the treatment of ITP.